In-frame versus out-of-frame Duchenne muscular dystrophy deletions: a comparative case report highlighting genotype–phenotype correlation in the therapeutic era - Balasubramaniam, Geerthana; Ramamurthy, Guhan (International Journal of Research in Medical Sciences, 2026)
Dystrophinopathies, including Duchenne muscular dystrophy (DMD) and Becker muscular dystrophy (BMD), are X-linked neuromuscular disorders caused by mutations in the DMD gene. We describe two male patients with dystrophinopathies due to large deletions in the DMD gene. Case 1 is a 23-year-old male with adult-onset proximal muscle weakness and preserved ambulation. Genetic analysis revealed an in-frame deletion of exons 45–48, consistent with Becker muscular dystrophy. Case 2 is a 7-year-old child presenting with early-onset progressive muscle weakness, a positive Gower’s sign, loss of ambulation, and markedly elevated creatine kinase levels. Multiplex ligation-dependent probe amplification (MLPA) identified an out-of-frame deletion spanning exons 46–57, confirming a diagnosis of Duchenne muscular dystrophy. Reading-frame status produced notably distinct clinical manifestations, despite the same gene and comparable mutational processes. The dystrophin reading-frame rule remains valid in this comparative case report, which also emphasises the importance of accurate molecular diagnosis for prognosis, genetic counselling, and treatment stratification in the era of precision medicine. To our knowledge, comparative genotype–phenotype case documentation from South Asian populations remains limited. This comparative case report adds valuable data from an underrepresented population.